Impact of Relationship Marketing on Customer Loyalty in Banking Sector of Pakistan - NOUMAN SAEED; DR. NAIMAT ULLAH KHAN (Journal of Business & Tourism, 2021)
This study is a contribution towards marketing literature by analyzing the impact of Relationship Marketing (RM) on Customer Loyalty. Every business organization tries to attract and retain customers for a longer period of time. In recent years an intense competition in banking sector of Pakistan is witnessed as the industry has stretched and become very competitive, where retaining customers in long run become important for every bank. Relationship marketing emphasizes on the continuity of long term relationship with the patrons. Numerous marketing strategies have been employed by banking sector to increase customer base, reduce turn over and to spread positive word of mouth of product and services. The aim of this study is to investigate the impact of relationship marketing practices such as (Trust, Commitment, Communication, Competence and Customer Satisfaction) on customer loyalty in Banking Sector of Pakistan. For this purpose, data is collected with the help of 150questionnaires across Pakistan. Statistical analysis is performed on the data using multiple regression analysis and reliability test. The results of the study show that all the five constructs of relationship marketing (mentioned above) have significant and positive relationship with customer loyalty. The factors are proved to be significant drivers of customer loyalty in banking sector of Pakistan. The study recommends that for retaining long-run customer loyalty, banks should consider relationship marketing as a core strategy. Hence, relationship marketing is important for banks to survive and excel in current intense competition.